(untitled) (REMUNOM, 2026)
The aim of this article was to characterize and propose an experimental combined training protocol for mice with diabetes. The study was conducted with male Swiss lineage mice (Mus musculus). The animals were randomly randomized into two groups: Normoglycemic Combined Group and Diabetic Combined Group. The induction of diabetes was carried out through the intraperitoneal administration of streptozotocin. The Combined Training Protocol (CTP) was characterized by the combination of Aerobic Training (AT) and Strength Training (ST). The AT presented a volume of thirty minutes of swimming. The ST protocol was carried out on a standardized ladder for resistance training in rodents, following a weekly progression prescription. The blood glucose measurement was measured in the tail tip region of each animal. The statistical analysis was carried out considering a significance level of p ≤ 0.05. Results of increased strength and consequently load progression with the CTP were observed, where a reduction in glycemia was also recorded during the studied period. The results highlight that the proposed experimental combined training protocol was effective in promoting a glycemic improvement and in promoting positive adaptations in muscle conditioning for models of mice with diabetes. diabetes.